Single-molecule quantum dot as a Kondo simulator - R. Hiraoka (Nature Portfolio, 2017)
Tuning the structure in the atomic scale enables manipulation of the quantum state in a molecular based system. Here, Hiraokaet al. tune the Kondo coupling between molecular spins and the Au electrode by controlling the position of Fe2+ions in the molecular cage with a tip.